Biological and physicochemical properties of bovine sodium caseinate hydrolysates obtained by a bacterial protease preparation - Hidalgo, María Eugenia (2014)
Fil: Fil: Hidalgo, María Eugenia. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Física Rosario (IFIR-CONICET); Argentina.